2014
DOI: 10.1007/s00240-014-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of reno-ureteral stone disease in Koreans: a nationwide population-based study

Abstract: The objective of this study was to evaluate the annual incidence of upper tract urolithiasis based on a large population-based study in Korea. This study used a subset of the 2009 Health Insurance and Review and Assessment service-National Patient Sample (HIRA-NPS). The 2009 HIRA-NPS contains data for 1,115,721 patients (711,285 inpatients and 404,436 outpatients) from January 2009 to December 2009. Based on these data, we selected patients who had been diagnosed with urolithiasis using the ICD code and calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 10 publications
4
29
2
Order By: Relevance
“…The annual incidence rate of ureter stones in Korea is 457 per 100 000. This rate is higher than that previously reported in Japan but lower than in Western countries [5].…”
Section: Introductioncontrasting
confidence: 47%
“…The annual incidence rate of ureter stones in Korea is 457 per 100 000. This rate is higher than that previously reported in Japan but lower than in Western countries [5].…”
Section: Introductioncontrasting
confidence: 47%
“…UUTC is highly prevalent in Korea and its prevalence is likely to increase (34). As in Western studies (101112), the number of patients undergoing active treatment for UUTC significantly increased over a 10-year period in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated lifetime prevalence rate in Seoul, Korea, was reported to be 3.5% in 1998 (6.0% in men and 1.8% in women) (3). In 2009, the annual incidence of UUTC in Korea was estimated to be 457 per 100,000 population, with 589.1 per 100,000 men and 326.6 per 100,000 women (4). Because of an increasingly Westernized diet, more sedentary lifestyle, and increase in obesity, the prevalence of UUTC in Korea is likely to increase.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study done by [26] who reported that in effective preventive measures, including specific pharmacological interventions in addition to advice for a change in lifestyle and nutritional habits are major factors for increasing recurrence rate of kidney stone. Moreover a study of [27] reported that the stone recurrence among the studied patients was 50% at 3 years after first kidney stone.…”
Section: Discussionmentioning
confidence: 99%